Human Rights Studies on Fulfillment of Restitution Rights for Children as Victims of Human Trafficking - Eva Syahfitri Nasution; Siti Nurahmi Nasution; M. Hadyan Yunhas Purba; Akmal Handi Ansari Nasution (Faculty of Law, Universitas Pekalongan, 2021)
This paper aims to analyze the fulfillment the restitution rights for the children as victims after the enactment of government regulation Number 43 of 2017 in Medan based on human rights studies. This research is normative legal research with statute approach which is carried out by examining law and regulations related to the legal issue being raised that is regarding the provision of restitution for child victim of human trafficking in Medan and empirical legal research which gaining data by means direct observation in Medan District Court. Based on the studies, it can be related that restitution must be given to the victims of human trafficking because it is a part of fulfillment of human rights to compensate the victim for losses suffered as the result of a crime.